Evaluation of a trilinear traction-separation law for mode II delamination using the effective crack method. (June 2019) - de Morais, A.B.
Abstract: Mode II delamination testing for measuring the critical strain-energy release rate has reached a high level of maturity with the recent publication of ISO and ASTM standards. Cohesive zone modelling has also become a well-established design tool implemented in many commercial finite element analysis codes. The particularly large fracture process zone in mode II delamination increases the relevance of the traction-separation law. This paper proposes a fairly simple inverse method to evaluate an approximate trilinear traction-separation law from quasi-static end-notched flexure test results. The method employs an analytical beam cohesive zone model and consists of evaluating the parameters that fit the effective crack length versus strain-energy release rate curve. Preliminary studies showed that specific features of the latter curve were quite sensitive to some model parameters. Therefore, accurate approximate trilinear traction-separation laws could be obtained without the extensive numerical calculations typical of inverse methods.